Escherichia coli and Klebsiella pneumonia as the Most Common Bacteria Causing Catheter Associated Urinary Tract Infection - Dwiyanti Puspitasari; Edward Adijaya Rusli; Dominicus Husada; Leny Kartina (Cell and BioPharmaceutical Institute, 2021)
Background: Healthcare-Associated Infections (HAIs) are the result of a reaction between taint agents that infected the patient when the patient is hospitalized. A Study from The Center for Disease Control and Prevention shows that most HAIs in hospital are urinary tract infection, most of the infection incident in patient are caused by catheter. Catheter indwelling is notable in medical sphere. This study aimed to inquire case number of Catheter-Associated Urinary Tract Infection (CAUTI) in Dr. Soetomo General Hospital, the feature of CAUTI patients, the type of bacteria that cause CAUTI, and what is the relation among sex and bacteria colony.Materials and Methods: An analytic observational study with the population of pediatric hospitalized patients of Dr. Soetomo General Hospital was conducted in January-December 2017. Samples collected were positive urine culture from pediatric hospitalized patients. Information regarding the bacteria that cause CAUTI, gender, and length of catheter usage were collected.Results: There were total 140 samples of positive urine culture in pediatric patient, and 38.5% was diagnosed as CAUTI. Overall CAUTI was often found in male subjects (51.9 %), and similar with ≤1-year old patients which also often found in male subjects (60.8%). The highest length of catheter usage was 3-5 days (42.5%). All subjects had fever as a clinical sign and 83.3% had suprapubic pain. Escherichia coli and Klebsiella pneumoniae infections were highly discovered. There was an association between gender and urine culture colony count (p=0.02).Conclusion: CAUTI is commonnly found in Dr. Soetomo General Hospital, and two bacteria that cause the most infection were E. coli and K. pneumoniae.Keywords: catheter, urinary tract infection, healthcare associated infection